Beyond the overall economic downturn: Evidence on sector-specific effects of violent conflict from Indonesia - Marc Vothknecht; Sudarno Sumarto (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper analyses the impact of violent conflict on economic growth using micro-level data from Indonesia. We compile a panel dataset at district level for the period 2002-2008, and disentangle the overall negative economic effect of violent conflict into its sectoral components. Our results reveal substantial differences across sectors, with the most detrimental impact evident in manufacturing industries and the service sectors. Further, the short-run impacts on growth appear to be only temporal, and some evidence for the 'phoenix effect' in the early post-conflict period is found. The construction sector, in particular, recovers soon once conflict ends, while manufacturing industries and the finance sector appear especially reliant on a lasting peace. A series of alternative specifications confirm the main findings of the analysis.
Keywords: O11; F51; 330; violent conflict; economic growth; Indonesia